Real world algebra : understanding the power of mathematics - Zaccaro, Edward (Bellevue, Iowa : Hickory Grove Press, 2001)
Explains the process of using algebra to solve word problems, with chapters on the language of algebra, geometry and algebra, proportions and algebra, physics, levers, the Pythagorean Theorem, percents and algebra, simultaneous equations, and algebra and money.
Adult
Adult
Keywords: Algebra -- Problems, exercises, etc; Word problems (Mathematics); Algebra -- Problems, exercises, etc; Word problems (Mathematics)